Effect of anions on removing Cu2+, Mn2+ and Zn2+ in electrocoagulation process using aluminum electrodes - Hanay, Ozge; Hasar, Halil (Elsevier Science Bv, 2011)
In the present study, the performance of electrocoagulation process with aluminum electrodes in the treatment of Cu2+, Zn2+ and Mn2+ containing aqueous solutions was investigated by depending on type of anion in solution, considering some operating conditions such as initial metal concentration and pH. Results obtained from synthetic wastewater showed that type of anion in solutions has a significant effect on the metal removal. The initial concentration of zinc influenced significantly the performance of electrocoagulation process as compared with the results obtained from Mn and Cu metals. Anions studied did not generate an important difference between pH variations. Best removals for three metals were achieved with increasing the pH in the presence of both anions. Total removals of copper and zinc reached almost 100% after 5 min at pH values > 7. At the end of the experiments for 35 min, the Mn removals were 85 and 80% in the presence of sulfate and chloride anions, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Heavy Metal; Electrocoagulation; Aluminum electrodes; Anions